Analisis kemampuan mahasiswa dalam menyelesaikan soal IPA tipe HOTS - Purwanti, Siwi (JIPVA (Jurnal Pendidikan IPA Veteran); Vol 4 No 1 (2020): JIPVA (Jurnal Pendidikan IPA Veteran)DO - 10.31331/jipva.v4i1.1102, 2020)
Students need to have high-level thinking skills to be able to deal with various developments in this century. This study aims to determine the ability of students to think in solving HOTS type science problems in advanced science courses. The subjects of the study were the 87 students of 6 th -semester PGSD students in the 2018/2019 school year. This study uses interview guidelines as well as HOTS-based test questions. Data analysis was performed using qualitative and quantitative methods. The results showed that in general students' high-level thinking skills reached 72.28% and included in the sufficient criteria. Students who can reach the C4 level (Analysis) reach 81.52%, C5 (Evaluation) 71.91%, and C6 (Creation) 60.67%. While the results of the interview show that students have difficulty in designing experiments, formulating problems, and completing experiments. Thus, it can be seen that the ability of PGSD students in solving HOTS type science questions needs to be improved, especially at the C5 and C6 levels.